Marine Actinomycetes screening of Banten West Coast and their antibiotics purification - ROFIQ SUNARYANTO; BAMBANG MARWOTO (Society for Indonesian Biodiversity, 2010)
Sunaryanto R, Marwoto B (2010) Marine Actinomycetes screening of Banten West Coast and their antibiotics purification. Biodiversitas 11: 176-181. Isolation and purification of active compounds produced by marine Actinomycetes has been carried out. Marine sediment samples were obtained from six different places at Anyer, Banten West Coast in October 20, 2007. Isolation was carried out using two methods pretreatments, acid treatment and heat shock treatment. A total of 29 Actinomycetes isolates were obtained from the various sediment samples collected, then tested for antimicrobial test against Escherichia coli ATCC 25922, Staphylococcus aureus ATCC25923, Pseudomonas aeruginosa ATCC27853, Bacillus subtilis ATCC 66923, Candida albicans BIOMCC00122 and Aspergillus niger BIOMCC00134. Identification of potential isolate was carried out using 16S rRNA. Purification of active compound was carriedout using silica gel column chromatography and preparative HPLC. Result of this research showed that isolate A11 produced the most active compound against Gram-positive and Gram-negative bacteria. Morphology and identification test using 16S rRNA gen showed that isolate A11 is Streptomyces sp. Production of active compound from isolate A11 used yeast peptone medium. The single peak of active compound was detected by HPLC and showed retention time on 8.35 min and maximum absorbance UV visible of antibiotic was 210 nm and 274.5 nm. Active purified compound showed inhibition activity to Gram-positive and Gram-negative bacteria. Minimum inhibitory concentration (MIC) to E. coli ATCC 25922 was 27 Î¼g/mL, P. aeruginosa ATCC 27853 68.7 Î¼g/mL, S. aureus ATCC 2592380.2 Î¼g/mL, and B. subtilis ATCC 66923 73.7 Î¼g/mL.Key words: marine Actinomycetes, isolation, screening, antimicrobial activity, minimum inhibitory concentration